Variation in nest characteristics and brooding patterns of female Black-throated Blue Warblers is associated with thermal cues. (6th June 2018) - Smith, Maria G.; Kaiser, Sara A.; Sillett, T. Scott; Webster, Michael S.
Abstract: Thermal variation poses a problem for nesting birds and can result in reduced offspring growth rates and survival. To increase the thermal stability of the nest, females can adjust nest characteristics and nest attendance in response to changes in environmental conditions. However, it is unclear how and to what extent females modify parental behaviors during various stages of offspring development. We tested the hypothesis that females adjust nest characteristics and brooding patterns in response to thermal variation during the nest-building and nestling stages, respectively. We examined elevational variation in nest location, nest construction, and brooding patterns in the migratory Black-throated Blue Warbler ( Setophaga caerulescens ) across a 2°C gradient at the Hubbard Brook Experimental Forest, New Hampshire, USA. Density of woody stems at nest sites and nest wall thickness increased from low to high elevation, corresponding to decreasing temperatures, but we found no relationship between weather during nest building and nest characteristics. However, weather during the nestling stage was associated with female brooding patterns: at lower temperatures and with higher rainfall, females spent more time off the nest, which was associated with lower nestling mass near fledging. These results suggest that thermal cues during nest building may be unreliable as predictors of future conditions for developing nestlings and also that females might favor their own self-maintenance and compromise nestling growth under adverse thermal conditions.